2002
DOI: 10.1172/jci0215751
|View full text |Cite
|
Sign up to set email alerts
|

Experimental autoimmune encephalitis and inflammation in the absence of interleukin-12

Abstract: Induction of EAE. Female C57BL/6 mice were obtained from NCI Laboratories (Frederick, Maryland, USA). Homozygous IL-12 p35-/and IL-12 p40-/-C57BL/6 mice were originally purchased from The Jackson Laboratory (Bar Harbor, Maine, USA) and were bred in-house under pathogenfree conditions. Female C57BL/6, IL-12 p40-/-, and p35-/mice 5-8 weeks old were immunized subcutaneously with 200 µg of MOG 35-55 peptide emulsified in CFA supplemented with 5 mg/ml of Mycobacterium tuberculosis (H37RA; Difco Laboratories, Detroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
188
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 343 publications
(198 citation statements)
references
References 25 publications
8
188
0
2
Order By: Relevance
“…Although surprising at first sight, a protective role of IL-12 in an inflammatory condition has been observed in other tissues, for example, in organ-specific autoimmune inflammation of the central nervous system. There, likewise to the clinical findings in our psoriasis model, IL-12 restrains part of the inflammatory response5354. Also in EAE a dual role of IL-12 is debated, as type 1 immunity is partially considered to be instrumental in disease progression and central nervous system pathology, but on the other hand the net effect of IL-12 is clearly anti-inflammatory.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Although surprising at first sight, a protective role of IL-12 in an inflammatory condition has been observed in other tissues, for example, in organ-specific autoimmune inflammation of the central nervous system. There, likewise to the clinical findings in our psoriasis model, IL-12 restrains part of the inflammatory response5354. Also in EAE a dual role of IL-12 is debated, as type 1 immunity is partially considered to be instrumental in disease progression and central nervous system pathology, but on the other hand the net effect of IL-12 is clearly anti-inflammatory.…”
Section: Discussionsupporting
confidence: 64%
“…Shortly after the discovery of IL-23 in 2003, however, it became apparent that the anti-p40 therapeutic approach inadvertently counteracted two major inflammatory pathways in parallel, IL-12 and IL-23. The predominant role of IL-23 in the pathogenesis of some chronic inflammatory disease, which was formerly claimed by IL-12, was first discovered in experimental autoimmune encephalomyelitis (EAE) a disease model for multiple sclerosis535455. Nonetheless, anti-p40 mAb therapy performed with unprecedented efficacy in treatment of plaque-like psoriasis for which it became FDA approved in 2009 (ustekinumab).…”
Section: Discussionmentioning
confidence: 99%
“…0, no clinical sign; 0.5, partial tail paralysis; 1.0, complete tail paralysis; 1.5, complete tail paralysis and discrete hind limb weakness; 2.0, complete tail paralysis and strong hind limb weakness; 2.5, unilateral hind limb paralysis; 3, complete hind limb paralysis; 3.5, hind limb paralysis and forelimb weakness; 4.0, complete paralysis (tetraplegia), and 5.0, moribund or dead [17, 18]. The successful induction of EAE in all mice in both groups was confirmed by this scoring scale.…”
Section: Methodsmentioning
confidence: 99%
“…IL-23 prolongs the expression of type 17 signature cytokines (such as IL-17, IL-22 and GM-CSF) that induce tissue pathology and mediates chronic inflammation by promoting the survival and maintenance of Type 17 cells [22, 24]. Thus it is notable that during neuroinflammation, IL-23 produced by CNS-resident cells maintains the pathogenic capacity of CNS-invading T cells while resistance of IL-23p19- and p40-deficient mice to EAE correlates with marked reduction of encephalitogenic T cells [25, 26]. Similarly, IL-23 receptor expression on γδ T cells is implicated in immunopathogenic mechanisms of EAU [27] and it has been suggested that IL-23 plays an important role in birdshot retinochoroidopathy [28].…”
Section: Interleukin 12 (Il-12) Cytokinesmentioning
confidence: 99%